LOSS LEARNING PADA SISWA SEBAGAI DAMPAK PANDEMI COVID-19 PADA MATA PELAJARAN IPA DI SMP NEGERI 7 TUBAN - Wulandari, Tabitha Sri Hartati; Wahyuni, Eti; Tumiar Panggabean, Christina Innocenti (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2022)
Corona virus diseases 2019 (Covid-19) had spread throughout the world including Indonesia. The high number of cases in Indonesia had impacts in various fields, including education, in which online learning was implemented, as a form of learning adaptation to reduce the spread of Covid-19 in Indonesia. The implementation of online learning had caused the phenomenon of Loss Learning, namely the existence of certain conditions that cause a decrease in students' mastery of competence, due to loss of knowledge and skills. This was triggered by a new learning atmosphere, where the students were not used to it.. This study aims at seeing the responses of SMP 7 Tuban students to the implementation of online learning to the occurrence of loss learning. This study applied a descriptive qualitative research. The data were collected by distributing questionnaires to 64 students from classes IX-A and IX-B in science subjects. The results showed that by implementing online learning 50% of students were not pleased, 31% of students said they were not quite pleased, and 19% of students were quite pleased with online learning. From these data it can be concluded that the responses of the students to online learning is low, because half of the students expressed displeasure. This condition can result in low learning motivation of the students and the loss learning phenomenon.